Entrepreneurial Identity: A Review and Research Agenda - Radu-Lefebvre, Miruna; Lefebvre, Vincent; Crosina, Eliana; Hytti, Ulla (Entrepreneurship Theory and Practice, 2021)
Over the past three decades, research on entrepreneurial identity (EI) has grown particularly rapidly, yet in seemingly disparate directions. To lend structure to this fragmented field of inquiry, our systematic integrative review maps and integrates EI research based on antecedents, content, outcomes as well as their relationships. In so doing, we reveal that the field revolves around two primary conceptualizations of EI as Property or Process. We suggest future avenues for examining the interplay between EI and temporal, socio-cognitive, and spatial contexts, and for investigating and theorizing overlooked mechanisms of reconstructing and losing EI.